The Initiation of Swallowing Can Indicate the Prognosis of Disorders of Consciousness: A Self-Controlled Study - Wang, Jianan; Wang, Jing; Hu, Xiaohua; Xu, Lingqi; Tian, Jinna; Li, Jiayin; Fang, Danruo; Huang, Wangshan; Sun, Yuxiao; He, Minhui; Laureys, Steven; Di, Haibo (Frontiers in Neurology, 2019)
Objective: To detect the initiation of swallowing in patients with disorders of consciousness (DOC) as well as the relationship between the initiation of swallowing and the prognosis of DOC patients. Methods: Nineteen DOC patients were included in this study, and a self-controlled trial compared five different stimuli. The five different stimuli were as follows: (1) one command, as recommended by the Coma Recovery Scale-Revised (CRS-R), which was “open your mouth”; (2) placing a spoon in front of the patient's mouth without a command; (3) placing a spoon filled with water in front of the patient's mouth without a command; (4) one command—“there is a spoon; open your mouth”—with a spoon in front of the patient's mouth; (5) one command, “there is a spoon with water; open your mouth,” with a spoon filled with water in front of the patient's mouth. All 19 patients were given these five stimuli randomly, and any one of the commands was presented four times to a patient, one at a time, at 15-s intervals. The sensitivity and specificity of the initiation of swallowing in detecting conscious awareness were determined. Results: None of the patients responded to the first four stimuli. However, six patients showed initiated swallowing toward the fifth stimulus. Among those six, five patients showed improvement in their consciousness state 6 months later. The sensitivity and specificity of the initiation of swallowing for DOC patients was 83.33% [95% CIs (36%, 100%)] and 92.31% [95% CIs (64%, 100%)], respectively. Conclusions: The initiation of swallowing can be an early indication of conscious behavior and can likely provide evidence of conscious awareness. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT03508336; Date of registration: 2018/4/16.